Management and treatment of dysphagia in intubated patients in the Greek-Cypriot ICU's. - Kyranou, Maria (My University, 2024)
Introduction: Post-extubation dysphagia (PED) can lead to serious health problems in vulnerable critically ill patients, yet routine bedside screening may be lacking in many Intensive Care Units (ICUs), possibly due to limited awareness for this condition. Objectives: The present study aimed to establish baseline data on the current approaches, the status of perceived best practices to PED management and treatment, as well as to assess awareness of PED and its consequences. The questionnaire was completed by a designated clinician, after consultation with the ICU team. Methods: A nationwide cross-sectional, online survey was conducted of all adult ICUs (n = 14; response rate 100%) in the Republic of Cyprus. Results: None of the included ICUs had a dedicated speech and language pathologist/ therapist (SLP/SLT). More than 85% of ICUs reported that there was no standard protocol indicating which patients should be screened for PED. Cough reflex testing and water swallow test were the most commonly reported assessment methods used to confirm the presence of PED. In the majority of ICUs (64.3%), nurses and intensivists were responsible to assess PED as well as SLP/ SLTs. Muscle strengthening exercises without swallowing and swallowing exercises were mostly used to treat dysphagia. Of the ICUs, 71.4% reported the need for standard protocols for PED screening. Overall, 28.6% of the ICUs agreed that PED was common in their unit. Conclusions: We identified gaps in Greek Cypriot ICUs awareness and practice regarding PED management, treatment, and consequences. Comprehensive unit-based dysphagia education programs must be urgently implemented. Interdisciplinary and collaborative work between nurses, intensivists and SLPs is needed to improve the quality of care provided.
Keywords: dysphagia, ICU, patients, management, treatment